Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/xen.12582
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation literature update, November/December 2019

Abstract: The ever-increasing disparity between the lack of organ donors and patients on the transplant waiting list is increasing worldwide. For the past several decades xenotransplantation has led the way to correct this deficit and remains clearly the only feasible option to provide a means to meet the demand for patients in need of an organ transplant. Xenotransplantation's ability to provide a specifically designed unlimited supply of organs, suited to treat the various needs for transplant organs and cells, has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Although xenotransplantation has been expected to serve as a potential solution to the chronic donor shortage in transplantation, its application has not progressed well due to concerns regarding immunological rejection and transmission of infectious diseases. The problem of immunological rejection has been resolved in recent years with the development of superior immunosuppressive drugs and advances in gene editing technology 35 , 36 , but there is still much uncertainty about the transmission of infectious diseases caused by known or unknown microorganisms. The prediction of the transmission of animal viruses to humans from in vitro or in vivo studies is difficult, and thus it is important to monitor the infection in the actual transplanted patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although xenotransplantation has been expected to serve as a potential solution to the chronic donor shortage in transplantation, its application has not progressed well due to concerns regarding immunological rejection and transmission of infectious diseases. The problem of immunological rejection has been resolved in recent years with the development of superior immunosuppressive drugs and advances in gene editing technology 35 , 36 , but there is still much uncertainty about the transmission of infectious diseases caused by known or unknown microorganisms. The prediction of the transmission of animal viruses to humans from in vitro or in vivo studies is difficult, and thus it is important to monitor the infection in the actual transplanted patients.…”
Section: Discussionmentioning
confidence: 99%
“…PERVs are integrated into the pig genome and could potentially integrate into the host‐genome, although this has not been reported in any clinical or preclinical trials utilizing pig tissue. But there are limited long‐term clinical trials reported to date following xenotransplantation and as such the findings from any long‐term studies are of interest to the xenotransplant community 44 …”
Section: Importance Of the Choice Of Correct Donor Animal And Tissuesmentioning
confidence: 99%
“…However, there are still 3 major barriers preventing successful pig-to-primate (human) organ transplantations: (a) Glycans on the surface of porcine endothelial cells act like xenoantigens (α-Gal, Neu5Gc, SDa) and cause hyperacute rejection (HAR), (b) dysregulated coagulation due to the disagreement between the pig and human coagulation system (THBD, TFPI, CD39), and (c) porcine endogenous retroviruses (PERVs) in porcine genome can transfer vertically into human cells and causexenosis. Due to the efficiency and simplicity of CRISPR gene editing, researchers have tested ~40 different combinations of pig-gene knock-out and human-gene knock-in into the porcine genome with great efficiency in less than a decade 51,52. Recently, G. Church and colleagues established the most advanced transgenic pig by using CRISPR technology in which they successfully deleted 3 pig genes (GGTA1, CMAH, and B4GALNT2), and specifically inserted 9 human transgenes (CD46, CD55, CD59, B2M, HLA-E, CD47, THBD, TFB1, and CD39) in a single locus in addition to the inactivation of 25 PERV loci in pig cells 53.…”
mentioning
confidence: 99%